2012
DOI: 10.1128/aac.00672-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo Biloba on the Pharmacokinetics of Raltegravir in Healthy Volunteers

Abstract: dMedicinal herbs may cause clinically relevant drug interactions with antiretroviral agents. Ginkgo biloba extract is a popular herbal product among HIV-infected patients because of its positive effects on cognitive function. Raltegravir, an HIV integrase inhibitor, is increasingly being used as part of combined antiretroviral therapy. Clinical data on the potential inhibitory or inductive effect of ginkgo biloba on the pharmacokinetics of raltegravir were lacking, and concomitant use was not recommended. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In general, the proof-of-concept clinical study suggested a low interaction risk of silibinin administered with raloxifene. These data are consistent with evaluation of herbal products as inhibitors of hepatic glucuronidation in healthy volunteers [43][44][45][46][47] and support the assertion that drug interaction risk for UGT substrates is generally low. 48 However, multiple subjects demonstrated nearly 2-fold increases in raloxifene exposure, suggesting that the interaction potential should not be disregarded entirely.…”
Section: Discussionsupporting
confidence: 88%
“…In general, the proof-of-concept clinical study suggested a low interaction risk of silibinin administered with raloxifene. These data are consistent with evaluation of herbal products as inhibitors of hepatic glucuronidation in healthy volunteers [43][44][45][46][47] and support the assertion that drug interaction risk for UGT substrates is generally low. 48 However, multiple subjects demonstrated nearly 2-fold increases in raloxifene exposure, suggesting that the interaction potential should not be disregarded entirely.…”
Section: Discussionsupporting
confidence: 88%
“…G. biloba exerting a significant inductive effect on CYP2C19, were found to induce omeprazole hydroxylation in a CYP2C19 genotype-dependent manner decreasing its potential efficacy in human ( 19 ). G. biloba increased the AUC of raltegravir, an HIV integrase inhibitor in humans by 21% and Cmax by 44% which is favorable ( 20 ). Meanwhile, these examples with reduced AUCs in humans are mainly at doses higher than the recommended standardized extracts by European Pharmacopeia ( 21 ).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In the clinical setting, pharmacokinetics of raltegravir have been shown to vary widely both within and between patients with no reported impact on safety . In this study no serious or severe AEs were reported and there were no discontinuations due to AEs.…”
Section: Discussionmentioning
confidence: 58%